Geochemical Analysis of Hot Springs in Massepe, Tellu Limpoe Sidenreng Rappang Regency, South Sulawesi Province, Indonesia - Arifin, M. Fauzi; Fachri, Hendra; Azikin , Busthan (The Islamic Education and Multiculturalism Foundation, 2023)
Location of the study is administratively located in the District Tellu Limpoe, Sidenreng Rappang Regency in South Sulawesi Province. Geographically located at coordinate 119°47'00